Sistem Pendukung Keputusan Penerima Beasiswa Dengan Metode Simple Additive Weighting (Studi Kasus di Fakultas Teknologi Informasi U.K. Maranatha) - Radiant Victor Imbar; Kevin Masli; Doro Edi (Jurnal Teknik Informatika dan Sistem Informasi, 2016)
Currently, the process of determining a scholarship at the Faculty of Information Technology Maranatha Christian University is still done manually. The existence of several types of scholarships offered, the number of defined criteria for each scholarship and the increasing number of students who enroll in order to receive the scholarship, causing the process of determining admission scholarship lasts longer and not objective. Based on the reasons above, this research is conduct using a decision support system that can provide recommendations to scholarship recipients. The assessment criteria of the applicants that much then used algorithms Fuzzy Multiple attribute Decision Making (Fuzzy MADM) with Simple Additive weighting method (SAW). The methodology used in the study consisted of three phases. The first stage is the preparation which includes the identification and formulation process of determining admission scholarship deploying along with the formulation of a decision support system requirements. At the second stage of implementation includes program development, testing, and implementation. While the last stage is the preparation of reports and research outcomes Keywords: achievement, Decision Support System, Maranatha Christian University, scholarship, Simple Additive Weighting